2023
DOI: 10.1017/s1041610223000935
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of cognitive “super-aging” in three Australian samples using different diagnostic criteria

Alice Powell,
Ben C.P. Lam,
David Foxe
et al.

Abstract: Objectives: To investigate the frequency of exceptional cognition (cognitive super-aging) in Australian older adults using different published definitions, agreement between definitions, and the relationship of super-aging status with function, brain imaging markers, and incident dementia. Design: Three longitudinal cohort studies. Setting: Participants recruited from the electoral roll, Australian Twins Registry, and community advertisements. Participants:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…First, we followed the most common approach used in previous research on SuperAgers, which is to classify high-performing older adults as participants above 60 years with memory scores above the average of the participants in the age-range 20 to 60 years (Powell, Page, Close, Sachdev, & Brodaty, 2023). Note that there is no uniform definition of SuperAgers, and a review reported that frequency of SuperAgers varies from 2.9% to 43.4% as a function of differences in definition (Powell, Lam, et al, 2023). It has been argued that a start age of 60 years, rather than 80 years, which was used in the original work on SuperAgers (Harrison et al, 2012), is problematic when the aim is to make meaningful statements about resilience and resistance to age-decline (Rogalski, 2019).…”
Section: Mri Preprocessing and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…First, we followed the most common approach used in previous research on SuperAgers, which is to classify high-performing older adults as participants above 60 years with memory scores above the average of the participants in the age-range 20 to 60 years (Powell, Page, Close, Sachdev, & Brodaty, 2023). Note that there is no uniform definition of SuperAgers, and a review reported that frequency of SuperAgers varies from 2.9% to 43.4% as a function of differences in definition (Powell, Lam, et al, 2023). It has been argued that a start age of 60 years, rather than 80 years, which was used in the original work on SuperAgers (Harrison et al, 2012), is problematic when the aim is to make meaningful statements about resilience and resistance to age-decline (Rogalski, 2019).…”
Section: Mri Preprocessing and Analysismentioning
confidence: 99%
“…Some older adults show superior memory function compared to same-age peers, and even perform on par with much younger persons (Powell, Lam, et al, 2023). These very high-performing older adults are sometimes referred to as SuperAgers (Harrison, Weintraub, Mesulam, & Rogalski, 2012).…”
Section: Introductionmentioning
confidence: 99%